FIRST AMONG EQUALS: A COMPARATIVE STUDY OF THE EFFECT OF HYDROCHLOROTHIAZIDE AND CHLORTHALIDONE ON RECENTLY DIAGNOSED HYPERTENSIVES - KUMAR, BIJAY; KAUR, SHARANJIT; MANZOOR, SAMI; JOT SINGH, HARINDER (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Thiazide diuretics have been the first choice to treat stable, uncomplicated, essential hypertension; hydrochlorothiazide (HCTZ) being the most preferred. Another thiazide, chlorthalidone is available since long and is reported to be equally efficacious if not better in treating primary hypertension. Aim: To compare the efficacy and safety of HCTZ and chlorthalidone in the management of primary essential hypertension. Methods: We compared these two drugs in a randomized, single-blinded, intention to treat study. Participants with essential hypertension received either chlorthalidone 12.5 mg OD or HCTZ 25 mg OD for a period of 12-week. The results were compared on the basis of 12 hourly ambulatory blood pressure (BP) monitoring; fortnightly record of serum potassium, and failure of treatment (i.e., the need of additional antihypertensive drug or incrementation in the dose of thiazides). Results: Out of 114,44 in chlorthalidone group and 39 in HCTZ group completed our study. There was a significant mean fall in BP by −11.89/−9.86 in the morning time and by −11.12/−7.56 in the evening time in group H receiving HCTZ 25 mg OD. In chlorthalidone group, this mean fall was by −16.45/−12.38 in the morning time and by −15.73/−10.86 in the evening time. After 12 weeks, night time BP control was better in chlorthalidone group (127.91±5.01) than HCTZ (132.67±5.19) (p=0.001). Both drugs decreased serum potassium levels, but this decrease was marginally more with HCTZ (3.777±0.601 vs. 3.891±0.534), statistically non-significant when compared to each other (p>0.05). Conclusion: Chlorthalidone is better than HCTZ in controlling BP throughout the day without causing any significant complication. Keywords: Diuretics, Antihypertensive effect, Hydrochlorothiazide, Chlorthalidone, Hypokalemia.